Design of natural-rubber panel railroad crossing using finite element method - Aunna Sukhom; Ittipol Jangchud; Monsak Pimsarn; Jarruwat Charoensuk; Veerachai Treeporncharoen (My University, 2018)
Thailand has a railway system that is available throughout the country, so there are several railroad crossings. These crossings are generally made of concrete or logs with multiple constraints. There are some disadvantages of concrete railroad crossing, such as, crack, noise during car passing over. To overcome these disadvantages, the softer materials should be used instead. Therefore, this research proposes the natural rubber, widely grown throughout Thailand, panel railroad crossing. However, the natural rubber alone is not enough to withstand the harsh condition. Thus, it is necessary to have some addition ingredients that will enhance the natural rubber properties. The material used in this research is a rubber compound between Chloroprene Rubber (CR) 75% and Natural rubber (NR) 25% blend with additives such as carbon black (CB), magnesium oxide (MgO) and sulfur (S8). The objectives of this article were to analyze the deformation of the natural rubber panel railroad crossing and to evaluate its safety factor, defined as the ratio of strain at break and the maximum equivalent strain, using finite element method. In the analysis, the applied loading of the model was obtained from the State Railway of Thailand. The analyzed results reveal that the deflection of rubber panels passes the standard from State Railway of Thailand. Safety factor of external rubber panel is 27.03 and for internal rubber panels are 9.12 and 15.29. The metal pads had elastically deformed and concrete railroad sleeper deformation was very small.
Keywords: Synthetic rubber; Structural Behavior of Reinforced Concrete